2010
DOI: 10.1590/s1415-52732010000400004
|View full text |Cite
|
Sign up to set email alerts
|

Evolução da massa corporal magra após 12 meses da cirurgia bariátrica

Abstract: ObjetivoO objetivo da pesquisa foi determinar a perda de massa corporal magra em pacientes após cirurgia bariátrica. MétodosO estudo retrospectivo foi conduzido com 17 prontuários de mulheres obesas submetidas à Derivação Gástrica em Y de Roux com anel de contenção gástrica, incluindo dados obtidos no período pré-operatório imediato e no 1º, 3º, 6º e 12º meses após a cirurgia. Os dados obtidos no prontuário incluíram a idade, medidas de peso, de altura e massa corporal magra e gorda, calculados pela impedância… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 20 publications
2
9
0
4
Order By: Relevance
“…According to Bouchard 3 resistance exercises can help obese to increase this rate (MCM) or at least slow its loss. This statement was confirmed when is compared the study of Cunha et al 5 , with the result of counter-kinesiotherapy resisted (this study), which gave an average loss of 43.86 kg of fat mass after the counter-resisted kinesiotherapy against an average of 39.8 kg, with a loss equivalent to 11% of MCM in the same time interval of six months.…”
Section: Discussionsupporting
confidence: 80%
“…According to Bouchard 3 resistance exercises can help obese to increase this rate (MCM) or at least slow its loss. This statement was confirmed when is compared the study of Cunha et al 5 , with the result of counter-kinesiotherapy resisted (this study), which gave an average loss of 43.86 kg of fat mass after the counter-resisted kinesiotherapy against an average of 39.8 kg, with a loss equivalent to 11% of MCM in the same time interval of six months.…”
Section: Discussionsupporting
confidence: 80%
“…These authors reported a similar reduction of 3.6 kg. Studies analyzing longer postoperative periods reported reductions in lean mass of 13.7 kg (17.5%) and 6.4 kg (10.4%) after 6 and 3 months, respectively 15,25 . The changes in nutrient absorption caused by surgery manifest in most cases as some type of nutritional deficiency.…”
Section: Discussionmentioning
confidence: 98%
“…These values are similar to those obtained in the present study. Fat mass reductions of 27.8 kg (40.5%) and 16.1 kg (24.4%) have been reported when the patients were followed up for a longer period of time after surgery (6 and 3 months, respectively) 15,25 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations